Hegemony in the Shadow of Post-Reality: Locating Common Sense in the Digitalocene - Lanfranchi, Benedetta (International Gramsci Journal, 2025)
This article investigates whether “the hegemonic form” theorised by Jean Baudrillard is currently being realised in the context of what is here tentatively called “the digitalocene”, drawing at liberty from Jason W. Moore’s formulation of the capitalocene that looks at capitalism not only as a system of production but as a system of life. The article questions whether the digitalocene is displacing historical understandings of what constitutes senso comune (common sense) and buon senso (good sense) among social groups as theorised by Antonio Gramsci, inhibiting the political ability to engage in counter-hegemonic intellectual and active practices.